Clinical Effects of Anterior Cervical Spondylolisthesis on Cervical Spondylotic Myelopathy After Posterior Decompression Surgery: A Retrospective Multicenter Study of 732 Cases. Issue 5 (June 2022) - Ninomiya, Ken; Yamane, Junichi; Aoyama, Ryoma; Suzuki, Satoshi; Shiono, Yuta; Takahashi, Yuichiro; Fujita, Nobuyuki; Okada, Eijirou; Tsuji, Osahiko; Yagi, Mitsuru; Watanabe, Kota; Iga, Takahito; et al.
Study Design: Multicenter retrospective study. Objectives: We aim to investigate features of cervical spondylotic myelopathy (CSM) associated with anterior cervical spondylolisthesis (ACS) during posterior decompression surgery. Methods: A total of 732 patients with CSM were enrolled, who underwent posterior decompression surgery between July 2011 and November 2015 at 17 institutions. The patients with ACS (group A), defined as an anterior slippage of ≥2 mm on plain radiographs, were compared with those without ACS (group non-A). Also, the characteristics of patients with ACS progression (group P), defined as postoperative worsening of ACS ≥2 mm or newly developed ACS, were investigated. Moreover, kyphosis was defined as C2-C7 angle in neutral position ≤−5°. The Japanese Orthopedic Association (JOA) scoring system was used for clinical evaluation. Results: Group A consisting of 62 patients (8.5%) had worse preoperative clinical status but comparable surgical outcomes to group non-A. Furthermore, ACS was associated with greater age, and the degree of slippage did not affect myelopathy grades. Seventeen patients (2.3%) were observed in group P, and preoperative ACS was a significant predisposing factor for the progression without clinical impact. Among the patients in group A, preoperative cervical kyphosis was a risk factor for lower JOA recovery rate. Conclusions: Although the presence of ACS increases the risk of postoperative progression, it is not a contraindication for posterior decompression. However, surgeons need to consider the indication of fusion surgery for the patients who have ACS accompanied by kyphosis because of the poor surgical outcomes.